Elementary Education in Chhattisgarh Status and Policy Perspectives - Padhi, Sambit Kumar (JOURNAL OF INDIAN EDUCATION, 2019)
Realising the importance of education in national development, momentum has been gathering in the last two decades all over the country for restructuring and consolidating education system in a bottom-up approach. Stringent initiatives have been taken to expand and strengthen elementary education as it marks an important phase in the life of school going children. In order to attain the goal of elementary education, every state has been putting enormous efforts, henceforth it is essential to know the scenario of elementary education in various states in general and Chhattisgarh in particular. Chhattisgarh is one of the newly formed states, and has no long history on elementary education. In this study, an attempt has been made to find out the growth of various types of elementary schools, enrolment of boys and girls, gross enrolment ratio, drop-out rate at various levels, teacher population and teacher-pupil ratio of Chhattisgarh from 2012–13 to 2016–17. This paper also highlights various implemented schemes by the state of Chhattisgarh such as, syllabus revision, computer literacy project, introduction of English language in Class I, appointment of teachers, training of in-service teachers, infrastructure facilities, distribution of free textbooks and uniforms, Mid-day Meal scheme, and insurance and scholarships for students to improve elementary education.